Rongjiang Bridge: The Longest Bridge of Rigid Girder and Flexible Arch. Issue 1 (2nd January 2021) - Sheng, Xingwang; Zheng, Weiqi; Dai, Jin; He, Ting
Abstract: Bridges of rigid girder and flexible arch have been widely used in the construction of high-speed railways in the last several decades. This bridge type is adopted for Rongjiang Bridge in Xiamen–Shenzhen railway. The main span of Rongjiang Bridge is 220 m, and it is the longest bridge of rigid girder and flexible arch in the world at present. The main structural design criteria and details of Rongjiang Bridge are introduced in this work, and the case features of this bridge are highlighted. Besides, some key issues associated with the structural design are researched, including the mechanical property of integral gusset plate, modal analysis and dynamic response of vehicle-bridge system. The multi-scale finite element modeling technique is recommended for analysis of the complex substructures, and the operating conditions of the vehicle-bridge system can be better evaluated by the co-simulation technology of multi-body dynamics and finite element method. Finally, a brief account of the construction method of this bridge type is reviewed.